Advances in Caribbean Andean bean breeding. - Beaver, James (2015)
Bean golden mosaic, rust, web blight, and common bacterial blight frequently limit bean (Phaseolus vulgaris L.) yield in the Caribbean. Results from the PROFRIJOL Caribbean Adaptation Nurseries demonstrate that CIAT and the bean breeding programs in the Caribbean have developed red mottled and light red kidney bean varieties with resistance to one or more of these diseases. The availability of molecular markers should permit the combination of specific genes conferring resistance. However, the effective use of these genes for disease resistance will require learning about the virulence patterns of pathogens. Sources of tolerance to some abiotic factors such as high temperatures have been identified. Nevertheless, bean breeding programs in the Caribbean have not yet developed bean varieties that combine disease resistance and tolerance to abiotic stress. The Dominican Republic, Haiti and Cuba have made collections of native Andean Caribbean bean varieties, which should prove to be the source of many valuable traits.